Improving the Quality of Reproduction and Quail Production (Coturnix coturnix japonica) with Liquid Probiotics - Emmy Susanti; Elly Tugiyanti (ANIMAL PRODUCTION, 2020)
This study aims to determine the effect of the use of various liquid probiotics in drinking water on the quality of the reproductive tract and quail production. The study uses a Completely Randomized Design with directional pattern with four treatments, namely: quail gets drinking water without liquid probiotics (P0), quail gets drinking water with commercial probiotics A (P1), quail gets drinking water with commercial probiotics B (P2), and quail gets drinking drinking water with commercial probiotics C (P3), 5 replications and 5 quails in each study unit. Drinking water is given ad libitum with a liquid probiotic concentration of 2ml / liter. Quail feed contains 22.2% PK and 3032.5 kcal energy. The treatment affected the weight of the reproductive tract + eggs, egg weight and length of the reproductive tract, weight before slaughtered, weight after slaughtered, weight after hair removal, heart weight, gastrointestinal weight, (P <0.01) but had no effect on carcass weight, liver weight, follicular weight, gizard weight, digestive tract length and caeca length. The treatment of liquid probiotics in drinking water increases several indicators of quail reproduction and production.